2009
DOI: 10.1177/0959683609104027
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy evidence of `Little Ice Age' palaeoenvironmental changes in a peat bog from northern Poland

Abstract: `Little Ice Age' (LIA) climatic deteriorations have been abundantly documented in various archives such as ice, lake sediments and peat bog deposits. Palaeoecological analyses of peat samples have identified these climatic deteriorations using a range of techniques, for example palynology, plant macrofossils, testate amoebae or carbon isotopic analyses. The use of inorganic geochemistry and the reconstruction of dust fluxes has remained a challenge in tracing the nature of LIA climatic changes. Although the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 67 publications
1
62
0
Order By: Relevance
“…The Scandinavian records were not acquired through geochemistry, but rather through the counting of mineral particles in the peat records; while in Poland, a highresolution geochemical study of an ombrotrophic mire allowed for the reconstruction of ASD using titanium as a conservative element. Both records were recently compared in De Vleeschouwer et al (2009) and de Jong et al (2010) and gave promising results, showing similarities in signals, in particular during the Little Ice Age (LIA) where enhanced ASD was recorded, suggesting increased erosion and wind storminess. However, considerable effort has to be devoted to assess enhanced ASD accurately during cold phases, especially because coastal areas are rich in easily erodible sand and finer material.…”
Section: Reconstruction Of Dust Fluxmentioning
confidence: 99%
See 2 more Smart Citations
“…The Scandinavian records were not acquired through geochemistry, but rather through the counting of mineral particles in the peat records; while in Poland, a highresolution geochemical study of an ombrotrophic mire allowed for the reconstruction of ASD using titanium as a conservative element. Both records were recently compared in De Vleeschouwer et al (2009) and de Jong et al (2010) and gave promising results, showing similarities in signals, in particular during the Little Ice Age (LIA) where enhanced ASD was recorded, suggesting increased erosion and wind storminess. However, considerable effort has to be devoted to assess enhanced ASD accurately during cold phases, especially because coastal areas are rich in easily erodible sand and finer material.…”
Section: Reconstruction Of Dust Fluxmentioning
confidence: 99%
“…4), mainly originating from the hydrosphere or the geosphere. Bromine and chlorine have been found in high amounts in oceanic mires De Vleeschouwer et al, 2009); however, these elements, which are highly enriched in sea salt sprays, are generally poorly retained by peat , although Biester et al (2004) demonstrated a close relationship between organohalogen concentrations and peat decomposition, a process strongly influenced by climate. Martínez-Cortizas et al (2007) showed a similar pattern with other major and trace elements.…”
Section: Sourcingmentioning
confidence: 99%
See 1 more Smart Citation
“…See text for explanation. the upper 1 m of several Misten peat cores emphasize the last millennium changes in vegetation, organic and/or inorganic geochemistry mainly recorded human perturbations (De Vleeschouwer et al, 2009, Allan et al, 2013a.…”
Section: Climate-related Dust Record In Misten Peat Bog Over the Histmentioning
confidence: 99%
“…Previous work has used peat cores as dust archives (Shotyk et al, 1998Bjö rck and Clemmensen, 2004;Martini and Martinez-Cortizas, 2006;Sapkota et al, 2007;De Vleeschouwer et al, 2009;Le Roux et al, 2012;Kylander et al, 2013). For instance Shotyk et al (1998) used the geochemical signature of peat to reconstruct the atmospheric particulate flux for the entire Holocene in a 6 m bog in the Swiss Jura.…”
Section: Introductionmentioning
confidence: 99%